Psychological impact of sports injuries and psychological well-being in relation to sports performance in competition gymnasts - Liberal, R.; Lopez-de-la-Llave, A.; Perez-Llantada, M. C.; Garcia-Mas, A. (Revista Portuguesa de Ciências do Desporto, 2014)
Investigations with athletes who have suffered injuries have always been associated to the physical aspects of the injury, and there has not been enough investigation on its psychological aspects and how they affect athletes` lives. The present paper examines the relationship between the psychological impact of a sport injury, psychological well-being and sports performance, before and after the injury, in 14 female gymnasts aged between 12 and 18 years old. Before the sport season begun, an adapted version of the Rating of Perceived Effort assessed the perceived psychological impact and the Spanish version of the Scale of Psychological Well-Being was used to assess psychological well-being. At the end of the season, the performance of the athletes, was compared to the results of the last season before the injury. Results were analyzed using descriptive and inferential statistics and showed a significant improvement in the overall athletic performance in the aftermath of the injury with respect to the previous season. However, there were no significant correlations between sports performance and the psychological well-being or the perceived psychological impact of the injury. Conversely, the results showed a positive relationship between the perceived psychological impact and the personal growth dimension of psychological well-being